SURVEI DIGITAL CONSUMER INSIGHT PADA GRUP WHATSAPP PASLIMO.ONLINE DITENGAH PANDEMI COVID-19 - Meirisca Yolanda Putri Endriz (2020)
As a result of the Covid-19 pandemic, social restrictions occur with the aim of stopping the spread of the Covid-19 virus. So there is a change in the way of meeting basic needs by utilizing online media as a buying and selling platform to meet daily basic needs. The purpose of this research, is to describe the consumer insight of consumers who are members of PASLIMO Whatsapp group online in meeting consumer basic needs in the middle of covid-19 pandemic. The theory used is the Reasoned Action Theory, and the method used is a quantitative method with descriptive research type. This research study took place in WhatsApp Paslimo.Online group. The population in the study was 249 members of the Paslimo.Online group using probability sampling techniques and the types of Simple Random Sampling samples were 71 respondents. This research is a one variable research (Univariate). Using descriptive analysis techniques with a percentage. The results of this study indicate that in the convention category (individual habits) get a percentage score of 32%. Cultural tension (individual tension / discomfort) gets a percentage score of 15%. Consumer motivation gets a percentage score of 56%.